(untitled) (Journal of the College of Languages (JCL), 2021)
Political terminology differs from any other type of terminology not only in the presence of political terminology, but also in content, structure, functions and the recipient who perceives it. Taking this into account, it is inappropriate to consider the semantic difficulties of translating Russian-language political terms solely at the semantic level. In our opinion, it is inextricably linked with the lexical, syntactic and grammatical levels. If we combine all 4 levels, then the following translation techniques can be distinguished: lexical borrowing (transcription / transliteration, tracing); modulation; generalization / concretization; omission / addition; descriptive translation; conversion [Komissarov 2013]. One of the most common methods to replenish the lexical composition of the language is foreign language borrowing. The process of borrowing foreign words into any recipient language is due to a complex of lingual and extra-lingual factors, the level of speech development and its structure, the completeness of the vocabulary in the recipient language [Srebryanskaya, 2020]. Аннотация Политическая терминология отличается от любого другого вида терминологии не только наличием политических терминосистем, но и содержанием, структурой, функциями и реципиентом, который ее воспринимает. Учитывая это, нецелесообразно рассматривать семантические трудности перевода русскоязычных политических терминов исключительно на семантическом уровне. По нашему мнению, он неразрывно связан с лексическим, синтаксическим и грамматическим уровнями. Если объединить все 4 уровня, то можно выделить следующие переводческие приемы: лексическое заимствование (транскрипция / транслитерация, калькирование);модуляция; генерализация / конкретизация; опущение / добавление; описательный перевод; конверсия [Комиссаров 2013]. Одним из самых распространенных способов пополнения лексического состава языка является иноязычные заимствование. Процесс заимствования иностранных слов в любой язык-реципиент обусловлен сложным комплексом лингвальных и экстралингвальных факторов, уровнем развития речи и ее структурой, полнотой словарного запаса в языке-реципиенте [Сребрянская, 2020].